PELAKSANAAN PROGRAM UPAYA KESEHATAN KERJA PADA POS UKK DI WILAYAH KERJA PUSKESEMAS KAMPUNG BUGIS KOTA TANJUNGPINANG KEPULAUAN RIAU - Mulyanto .; Halinda Sari Lubis; Isyatun Mardiyah Syahri (Lingkungan dan Kesehatan Kerja, 2013)
The implementation of occupational health efforts program at Pos UKK in the workplace of Kampung Bugis Health Center Tanjungpinang City Riau Islands. The main program of occupational health efforts Pos UKK is to provide preventive and promotive services to the workers members. Pos UKK cadre expected to implement health efforts program well. The problem in this research is, how the occupational health efforts program implemented at Pos UKK in the workplace of Kampung Bugis Health Center. This research is a qualitative research method, in order to get more in-depth information about the implementation of occupational health efforts program at Pos UKK. Informants in this study were 6 people, which 2 people from the Pasir Putih Pos UKK (chairman and members), 2 people from Sehat Sejahtera Pos UKK (chairman and members), and 2 people of the Sejahtera Mandiri Post UKK (chairman and members). The results showed that the occupational health efforts program in Pos UKK Kampung Bugis Health Centre workplace still held by the cadre. However, the implementation wasn’t optimal. The main program of occupational health efforts Pos UKK (health promotion and preventive) can not be carried out by a cadre of Pos UKK. Pos UKK cadres can only perform curative service. This is due to lack of knowledge and understanding of the role and function of cadres Pos UKK especially about health promotion and preventive. This condition also can not be separated from the role of Kampung Bugis health centers to the Pos UKK auxiliaries.The small sources of financial inclusion in Pos UKK in the workplace of Kampung Bugis Health Center also cause this condition. Coaching and training on the role and functions of Pos UKK cadres (primarily promotion and preventive) are continuous and sustainable to be implemented by the health centers Kampung Bugis in order to improve the knowledge and skills the cadres of Pos UKK. Landing and assisted health workers of Kampung Bugis Health Centre need to upgrading to the successful occupational health efforts program implemented at Pos UKK in the workplace of Kampung Bugis Health Center. Keywords: occupational health efforts, Pos UKK, Program Implementation